Oil Field Chemicals. - Fink, Johannes (Elsevier, 2003)
Oil field chemicals are gaining increasing importance, as the resources of crude oil are decreasing. An increasing demand of more sophisticated methods in the exploitation of the natural resources emerges for this reason. This book reviews the progress in the area of oil field chemicals and additives of the last decade from a rather chemical view. The material presented is a compilation from the literature by screening critically approximately 20,000 references. The text is ordered according to applications, just in the way how the jobs are emerging in practice. It starts with drilling, goes.